2019
DOI: 10.1038/s41598-019-52073-0
|View full text |Cite
|
Sign up to set email alerts
|

Association study of AGO1 and AGO2 genes polymorphisms with recurrent pregnancy loss

Abstract: An Argonaute (AGO) protein within the RNA-induced silencing complex binds a microRNA, permitting the target mRNA to be silenced. We hypothesized that variations in AGO genes had the possibility including affected the miRNA function and associated with recurrent pregnancy loss (RPL) susceptibility. Especially, we were chosen the AGO1 (rs595961, rs636832) and AGO2 (rs2292779, rs4961280) polymorphisms because of those polymorphisms have already reported in other diseases excluding the RPL. Here, we conducted a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…More than 65 genetic variants in 45 genes were identified that could be considered as risk factors for iRPL (Table 1). 13–59 The time frame of the sample is not mentioned in the studies because it does not involve a variable marker. Epigenetic factors, mainly microRNAs (miRNAs), that could also be considered as risk factors are compiled in Table 2 60–64 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 65 genetic variants in 45 genes were identified that could be considered as risk factors for iRPL (Table 1). 13–59 The time frame of the sample is not mentioned in the studies because it does not involve a variable marker. Epigenetic factors, mainly microRNAs (miRNAs), that could also be considered as risk factors are compiled in Table 2 60–64 .…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in DICER , DROSHA 49,51 ; miR‐125 52 ; miR‐27a , miR‐449b 54 ; miR‐423 55 ; AGO ‐1 59 ; and MTRR 30 have also been correlated with the condition. However, no association was found for DICER (rs3742330); DROSHA (rs10719); XPO5 (rs11077) 51 ; RAN (rs14035) 109,110 ; and lncRNA CCAT2 (rs3843549) 58 .…”
Section: Resultsmentioning
confidence: 99%
“…4e), validating the binding affinity of miR-5194 and LINC01063 in melanoma cells. According to previous literature, AGO2 has been identified as a cytoplasmic protein within the RNA-induced silencing complex, and can bind with miRNAs [39,40]. Thereby, we carried out an RIP assay, noticing that LINC01063 and miR-5194 coexisted in the same RISC complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As Ago2 works as one of RNA-induced silencing complex (RISC) components, 22 an Ago2 protein within the RISC complex could bind to an miRNA, for which the binding affinities of miRNA-Ago2 complexes have been confirmed. 23,24 Hence, Ago2-RIP assays were performed, and we found that circKIAA0368, miR-6838-5p, and HOXA10 mRNA all existed in the RISC (Figure 4E). The binding sites of miR-6838-5p on circKIAA0368 and HOXA10 mRNA were predicted by starBase (Figure 4F).…”
Section: Circkiaa0368 Sponges Mir-6838-5p To Upregulate Hoxa10 In Npc...mentioning
confidence: 93%